La muerte como experiencia mistérica. Estudio sobre la posibilidad de una experiencia de muerte ficticia en las iniciaciones griegas* - Martín Hernández, Raquel ('Ilu. Revista de Ciencias de las Religiones, 2005)
The mystical initiations have always conveyed the knowledge of the Underworld for their initiates and the happiness of the mistae in the after life. Throughout this paper we want to develop the idea of the existence of ritual death within the mystical initiations in Greece, focusing our attention on the Eleusinian and Orphic ones. We will also take notice of the distinctive form of consulting within the Trophonion’s oracle, which probably, led to the belief of the existence of mystical initiations in the cavern of Lebadea.
Keywords: Mysteries; ritual death; Eleusis; Trophonion oracle; orphism; Derveni papyrus